(untitled) (Bangladesh Journal of Plant Taxonomy, 2021)
The present study aims to evaluate the present status of plant species diversity in the road dividers of Dhaka city. A total of 90 plant species under 73 genera and 42 families have been recorded from the road dividers of Dhaka city. Analysis showed that among the 90 species, the most abundant plant species in the road divider are Mimusops elengi (Bakul) Polyalthia longifolia (Debdaru), Leucaena leucocephala (Epil-epil), Tabernaemontana divaricata (Togor) and Swietenia mahagoni (Mahagoni). In case of dominant analysis based important value index showed that Mimusops elengi is the top dominant plant species followed by Polyalthia longifolia, Leucaena leucocephala, Tabernaemontana divaricata and Swietenia mahagoni respectively. These plant species have also showed the higher relative density, relative frequency and relative abundance. The percentage of native and exotic species was found here 44% and 56%, respectively. Most abundant and dominant plant species in the road dividers are exotics including Mimusops elengi,Polyalthia longifolia, Leucaena leucocephala and Swietenia mahagoni. Species diversity value was found higher in Hatirjeel site whereas lowest in Baridhara- Badda site. A number of recommendations are made based on the present results for the management of plant species diversity in the road dividers of Dhaka city. Some recommended native plant species for plantation according to the width and soil depth in the road dividers are Cassia fistula, Holarrhena pubescens, Firmiana colorata, Shorea robusta, Miliusa valutina, Butea monosperma, Alstonia scholaris, Toona ciliata, Ficus racemosa, Bombax ceiba, Woodfordia fruticosa, Melastoma malabathricum, Sterculia villosa, Grewia microcos, Syzygium cumini, Tabernaemontana divaricata, Ixora coccinea, Terminalia bellirica, Terminalia arjuna and also native seasonal flowers. Bangladesh J. Plant Taxon. 28(1): 141-154, 2021 (June)